The Impact of Hyperledger Fabric Setup on Blockchain Performance when Using Large Volumes of Heterogeneous Medical Data - Spengler, Ana Caroline Fernandes; Souza, Paulo Sérgio Lopes de (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais do XXIV Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2023.235910, 2023)
Blockchain can be seen as a data distribution tool that guarantees immutability. As its use continues to expand across various sectors, it becomes increasingly important to investigate Blockchain’s performance concerning its different components and data originating from diverse application domains. This study explores the blockchain ecosystem, focusing on block creation, validation, network size, and partition processes. The chosen methodology involves utilizing Hyperledger Fabric for sharing medical information. To assess performance, Hyperledger Caliper was employed to collect throughput and latency. Among the key findings, we show that segregating the network into channels impacts the performance of Blockchain, mainly when the number of participating nodes increases. Sizes and timeouts to create new blocks influence the system’s performance. This paper contributes to developers by highlighting factors impacting blockchain-based applications’ performance.